Development of mobile application with geolocation technology for car service workshop / Nor Arzami Othman ... [et al.] - Othman, Nor Arzami; Osman, Mohd Nizam; Sedek, Khairul Anwar; Mohd Bohari, Muhammad Farid (UiTM Cawangan Perlis, 2022)
Mobile application with geolocation function has been on the market for quite some time. It has been implemented on most of the application to detect the user current location. With the lack of use and awareness of this features, we took that opportunities to develop mobile app and collaborate with YS Auto Workshop. It will detect the customer current location when they request for car breakdown from YS Auto workshop. Notification will be sent to the manager of the workshop and can see the marker on user current location and take an action. Main objectives are to design and develop mobile app and to evaluate its usage using user acceptance test in improving the user needs. Agile methodology has been used based on requirement and it is suitable in the development of mobile application. The development of the system has use agile method which has fifth phases including planning, analysis, design, development, and testing. Three expert users involve during Functionality Testing meanwhile thirty random selected respondents from district of Batang Kali involved in the experiment and perform Heuristic Evaluation and User Acceptance Test questionnaires. Analysis shown that application is interesting and helpful. The system is developed successfully and can make more improvement for the future.